2020
DOI: 10.1002/smll.202002311
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Yolk–Shell Encapsulation: Catalytic, Photothermal, and Sensing Demonstration

Abstract: Here, a novel, versatile synthetic strategy to fabricate a yolk–shell structured material that can encapsulate virtually any functional noble metal or metal oxide nanocatalysts of any morphology in a free suspension fashion is reported. This strategy also enables encapsulation of more than one type of nanoparticle inside a single shell, including paramagnetic iron oxide used for magnetic separation. The mesoporous organosilica shell provides efficient mass transfer of small target molecules, while serving as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…With respect to the suggestions that tight spatial confinement can either facilitate ion–surface electron transfer or avoid surface charge recombination during photoirradiation, new combinations of nanoreactors with external electro- or photoenergies may be explored. Nanoconfinement effects may stimulate the production of multifunctional nanomaterials with both spatial functionality and environmental considerations, such as emerging yolk–shell architecture with internal network catalysts that are also designed for convenient separation after use by incorporating magnetic nanoparticles . Although the use of nanoconfinement in the environmental field is still in its infancy, this review, through the examination of interesting case studies, generalized fundamentals, and potential implications and opportunities, can stimulate future research and breakthroughs for environmental nanoconfinement applications, bringing new concepts and expectations to light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the suggestions that tight spatial confinement can either facilitate ion–surface electron transfer or avoid surface charge recombination during photoirradiation, new combinations of nanoreactors with external electro- or photoenergies may be explored. Nanoconfinement effects may stimulate the production of multifunctional nanomaterials with both spatial functionality and environmental considerations, such as emerging yolk–shell architecture with internal network catalysts that are also designed for convenient separation after use by incorporating magnetic nanoparticles . Although the use of nanoconfinement in the environmental field is still in its infancy, this review, through the examination of interesting case studies, generalized fundamentals, and potential implications and opportunities, can stimulate future research and breakthroughs for environmental nanoconfinement applications, bringing new concepts and expectations to light.…”
Section: Discussionmentioning
confidence: 99%
“…Various structures with much larger pores than mesoporous silica have been used as synthetic templates demonstrating nanoconfinement effects on topological self-assembly of guest molecules (e.g., groove-patterned silica with 233 nm width for a growth of well-ordered copolymer nanospheres) and high-temperature crystallization (e.g., layered silica thin films with mean diameters of 32–140 nm for the synthesis of nickel oxide nanoparticles) . Another notable example is porous silica in the form of hollow nanospheres, which have been used as a nanoreactor for various applications, including the release of hydrogen from ammonia borane used in hydrogen storage and catalytic hydrogenation …”
Section: Nanoconfinement Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The existence of the cavity between the shell and the yolk allows sufficient exposure of the core while retaining the intrinsic properties of the core and shell in the maximum degree . Moreover, the cavity can serve as a host space to accommodate guests for special applications. , Particularly, in catalysis, compared to the core–shell structure, the cavity not only enables to expose more active sites for the reactants , but also provides a special microenvironment for heterogeneous catalysis. ,, Generally, the properties of functional materials very much depend on their compositions and structures. , Although the attractive performance can be realized by yolk–shell composites, it is always difficult to further systematically optimize their performance, as it is infrequent to use tailorable materials to serve as functional cores and shells. Therefore, it is highly desirable to construct novel yolk–shell composites with tailorable properties of both core and shell for diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, our group reported a versatile method to encapsulate any kind of metal/metal oxide nanoparticles in hollow mesoporous silica nanocapsules and demonstrated the photothermal, catalytic, and sensory applications of this method. 25 Although Lin et al reported a therapeutic nanoplatform by assembling AuNSs to apply it to photothermal and photodynamic therapy, the application of yolk−shell-type gold nanoaggregates with robust structures for chemo-and photothermal combination therapy has not yet been studied. 26 In this study, we developed an aggregated gold nanosphereencapsulated yolk−shell structure (aAuYS) with high structural uniformity by precisely controlling the AuNS loading concentration.…”
Section: Introductionmentioning
confidence: 99%